Pengaruh Kepemimpinan Instruksional Kepala Sekolah terhadap Kinerja Guru: Kajian Literatur - Rifka Jalal; Ernawati Ernawati; Jonni Mardizal (Journal on Education, 2025)
This study aims to explore the influence of principal leadership style on teacher performance in Vocational High Schools (SMK) through the Systematic Literature Review (SLR) approach. This study involved 10 articles published in the period 2019–2024 using the keywords "principal leadership," "teacher performance," and "SMK." The results of the review indicate that principal leadership styles such as instructional, transformational, participatory, and collaborative have a significant impact on various aspects of teacher performance. Instructional style focuses on supervising the learning process and curriculum development to ensure teaching effectiveness. Transformational leadership increases teacher work motivation, creativity, and commitment through an inspirational and reward-based approach. In addition, collaborative and participatory styles encourage the creation of an inclusive work atmosphere, which increases job satisfaction and encourages joint decision-making between teachers and principals. This study concludes that the success of implementing leadership styles is greatly influenced by the principal's ability to adjust their leadership style to the specific needs of teachers and the school context. These findings are expected to be a practical guide for principals to improve the quality of education in SMK.